Knowledge of oxygen delivery among paediatric trainee doctors and experienced paediatric nurses. (29th September 2015) - Rose, C; Heward, Y; McCabe, A; Duncan, H
Abstract : Aims: Assess the knowledge of oxygen delivery among paediatric junior doctors and nurses. Methods: A paper survey was developed, piloted, refined and completed by junior doctors at induction to a children's hospital, and experienced paediatric nurses attending post registration courses. The purpose was to identify and direct address knowledge gaps. Respondents needed to identify various oxygen delivery devices (nasal cannulae, face mask, face mask and reservoir bag, head box, tracheostomy mask, bag-valve-mask (BVM) and Ayre's T-piece), specify maximum percentage (%) of oxygen that can be delivered, flow rates required, use with spontaneously breathing patients and possibility of delivering continuous positive airway pressure. Results: A total of 152 surveys were completed, 29 of these by nurses. Identification: Nasal cannulae, tracheostomy mask and BVM were correctly identified 98%, 89% and 94% of the time. There was confusion over headbox (63% correct), face mask and reservoir bag (22% correct) and Ayre's t-piece (36% correct). Knowledge of maximum % oxygen delivered by each device was poor: nasal cannulae had 28% (32/114) correct answers; 42/114 responded that nasal cannulae delivered >40% oxygen. BVM and Ayre's T-piece had the most correct answers (69% and 82%). Flow rate responses showed poor knowledge of carbon dioxide clearance with oxygen delivery: 30% (37/125) would give <4l/min through a face mask, 30% (28/92) <5l/min through head box, and 31% (42/136) would put <10l/min through a face mask and reservoir. Only 46% would use 15l/min oxygen through a face mask and reservoir, and only 40% would use 15l/min oxygen with a BVM. Most responses correctly identified devices to use with spontaneously breathing patients. Some erroneously stated nasal cannulae (3/150), face masks (3/148) and head box (8/136) were not suitable for spontaneously breathing patients. 19 responses (13%) identified BVM as suitable for breathing patients. Conclusion: There are significant knowledge gaps regarding oxygen therapy despite their frequent use. Maximum % oxygen delivery and flow rates were particularly poor, with potential negative impact on patient care including: delivering too little oxygen in emergencies with BVM and face masks and reservoir, or too low flow rates with face masks and head boxes leading to CO2 retention. The correct use of BVM requires particular clarification. This survey informed interactive teaching focusing on this common, important and life-saving therapy.